The Artistry and Beauty of Coastal Batik: The Unique Identity and Significance of Lasem Batik - Suminto, RA Sekartaji (Proceeding Bali-Bhuwana Waskita: Global Art Creativity Conference, 2023)
This research aims to explore and highlight the cultural significance of Batik in the Indonesian archipelago, highlighting the unique characteristics of Batik Lasem as a renowned coastal batik variety. The study involves extensive research and documentation of the cultural heritage of Batik, focusing on Batik Lasem. Various historical records, literature, and cultural resources were reviewed and analyzed to gather comprehensive information. The research findings underscore the intrinsic value of Batik as an enduring cultural tradition in Indonesia. Batik Lasem, with its distinct features such as the use of the rare "red blood" color derived from noni tree roots and the Tumpal Pusung motif, stands out as a testament to the rich cultural heritage of the region. The research sheds light on the importance of preserving and promoting the unique cultural elements of Batik Lasem. This coastal batik not only reflects the cultural diversity of Indonesia but also serves as a symbol of cultural identity and pride, contributing to the ongoing appreciation and safeguarding of Batik as a priceless cultural heritage.